Perubahan Sifat Fisik Kimia Tanah Sebagai Dampak Kebakaran Lahan Gambut Kebun Sawit - T Abu Hanifah; Sofia Anita; Idwar Idwar (Universitas Riau, 2023)
Based on the survey results in the last seven years (2010 - 2017), palm plantations in the Pakning Asal area, Bengkalis Regency experienced fires with different frequencies. Some lands that not burned, once burned and several times burned. The burned areas can affect the composition and nutrient content of the soil. Burning peatlands cause irreversible drying due to the heating of the peat. This study aimed to analyze the effect of fires with different frequencies on the total Fe, Al, Mo and C/N content. Total Al and Mo content was determined using Atomic Absorption Spectrophotometer. The total Fe and C content was analyzed using UV-Vis Spectrophotometer. Total N was analyzed using the Kjeldahl method. The results showed that the total Fe, Al, and Mo content increased in the soil burned once and the C/N ratio increased with the increasing frequency of fires. The total Fe, Al, and Mo content in the soil burned once was 69.20 mg/Kg, 33.83 mg/Kg, 2.16 mg/Kg and the C/N ratio increased from 16.51 to 25.31, respectively. The impact of different fire frequencies affected the chemical content of the soil. Land fires have positive and negative impacts. The positive impact increased pH of soil palm plantations, while the negative impact caused air pollution and damage to soil structures.